A comparative study of hardness/scratch/wear properties of TiCN and TiAlN coatings on DIN 1.2842 steel by CA-PVD method - Simsir, Mehmet; Palaci, Yuksel; Ozer, Ali (SPRINGER, 2021)
In the present study, TiCN and TiAlN were deposited on DIN 1.2842 (AISI O2) steel, and their mechanical properties was compared by investigating coating thickness, adhesion strength, microhardness, and elastic modulus. To carry out characterizations, micro-wear test, Rockwell C adhesion, microhardness test, and scratch test were applied on TiCN- and TiAlN-coated DIN 1.2842 (AISI O2) steel. Deposition of the TiCN and TiAlN coatings was carried out on the hardened steel substrates (55-57 HRc) at 450-500 degrees C by cathodic arc physical vapor deposition (CA-PVD) method. As a result of the applied tests, adequate adhesion strength was obtained for both hard coatings. Through thickness microcrack, buckling failure mode and buckle spallation failure mode are observed at critical loads as Lc1, Lc2, and Lc3, respectively. TiAlN coating has better indentation hardness properties and elastic modulus. Wear resistance of TiAlN coating is better than that of TiCN coating due to similarity with substrate and tougher metallic character.
Keywords: PVD; TiCN; TiAlN coatings; Steel; Adhesion strength; Microhardness; Wear; Materials Science